0974 Sleep Training Outcomes of Mexican Diabetes Educators and Nursing Students. (12th April 2019) - Baldwin, Carol M; Ornelas, Luxana Reynaga; de la Cruz, Carolina Cabrera; Quan, Stuart F; Gamino, Sergio Marquez
Abstract: Introduction: This work provides outcomes of an evidence-based Spanish-language sleep education program for two groups at a university in central Mexico. Methods: Advanced training in sleep disorders and sleep health promotion was adapted from a lay health educator progam. Data stemmed from pre/post ratings regarding knowledge of obstructive sleep apnea (OSA), insomnia, restless legs syndrome (RLS), short sleep duration (SSD), circadian rhythm disorders (CRD), and drowsy driving (DD) on a 5-point Likert-like scale, and five true/false questions regarding misconceptions about sleep. Data were analyzed with frequencies for profession, sex, and sources of sleep information, and paired t -tests using SPSS (V24) with significance set at p <.05. Results: Volunteer participants (N=164; 72% women) were recruited from five semester-long diabetes educator certificate programs (n=127; doctors, nurses, nutritionists, exercise, mental health specialists) and an undergraduate nursing class (n=37). There were no differences for any variables between student and certificate groups; therefore, survey data were combined. Means with standard deviations showed significant learning for all sleep disorders across groups following the training (OSA: 2.6±1.0 to 4.4±0.79; Insomnia: 3.1±0.84 to 4.5±0.71; RLS: 1.6±0.87 to 4.3±0.84; SSD: 2.6 ±1.0 to 4.4±0.68; CRD: 2.2±1.0 to 4.3±0.76; DD: 2.4±1.0 to 4.4±0.71, all p <.0001). The total pre- to post-scores (range=0 to 30) for sleep disorders moved from 14.4±4.0 to 26.3±4.0, p <.0001. Participants also demonstrated significant learning regarding misconceptions about sleep pre- 4.2±0.70 to post-testing 4.8±0.41, p <.0001. Respondents reported most of their sleep information came from the internet (33%), doctors (26%), and books (15%) or articles (15%). Conclusion: Results suggest that this evidence-based Spanish-language sleep program is a salient and cost-effective approach to preparing diabetes educators and undergraduate nursing students regarding sleep disorders across the lifespan in Mexico. Pre-to-post analyses of true/false items suggest significant learning in the areas of sleep needs for adults and the misconception that daytime sleep can make up for lack of sleep at night. Given the high prevalence of DM in Mexico, the behaviorally based sleep promotion strategies included in the training could help decrease sleep-associated comorbidities, thereby reducing health care costs. Support (If Any): N/A